2018
DOI: 10.1074/jbc.m117.811471
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitinated CD36 sustains insulin-stimulated Akt activation by stabilizing insulin receptor substrate 1 in myotubes

Abstract: Both the magnitude and duration of insulin signaling are important in executing its cellular functions. Insulin-induced degradation of insulin receptor substrate 1 (IRS1) represents a key negative feedback loop that restricts insulin signaling. Moreover, high concentrations of fatty acids (FAs) and glucose involved in the etiology of obesity-associated insulin resistance also contribute to the regulation of IRS1 degradation. The scavenger receptor CD36 binds many lipid ligands and its contribution to insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…To further explore the molecular mechanism of UCHL1 on the regulation of CD36, we observed the inhibition of UCHL1 promotes CD36 degradation. Previous study has demonstrated that CD36 degradation involved in ubiquitin system 20 . We supposed whether decreased CD36 expression induced by UCHL1 is associated with UPS.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To further explore the molecular mechanism of UCHL1 on the regulation of CD36, we observed the inhibition of UCHL1 promotes CD36 degradation. Previous study has demonstrated that CD36 degradation involved in ubiquitin system 20 . We supposed whether decreased CD36 expression induced by UCHL1 is associated with UPS.…”
Section: Discussionmentioning
confidence: 95%
“…CD36, one of scavenger receptor class B family, in addition to the major function in facilitating lipid uptake by macrophages, could bind some ligands, such as thrombospondin-1, oxLDL, apoptotic cells, and cell-derived microparticles 34 . The expression of macrophage CD36 is increased by inhibiting lysosomal and proteasome, suggesting the regulation of CD36 level associates with the ubiquitin pathway 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IRS-1, the critical molecule downstream of the insulin and the insulin-like growth factor 1 receptor 64 , can be ubiquitinated by the CUL7 E3 ligase, suggesting that such tumor-suppressive activity might be related to CUL7-mediated targeted degradation of IRS-1. Recently, Sun et al revealed that CD36 could negatively regulate insulin activation, indicating that CD36 interacted with IRS-1, thereby abrogating the binding between IRS-1 and CUL7, which would further increase IRS-1 stability and affect insulin signaling 65 and might ultimately result in tumor suppression. In addition, the level of the voltage-gated potassium channel Eag2, which promotes cell migration in medulloblastoma 66 , 67 , is dramatically decreased by CUL7 overexpression 68 , which might also suppress the progression of tumors.…”
Section: Cul7 In Cancermentioning
confidence: 99%
“…TGFβ and PDGF have been reported to promote biglycan expression through AKT activation [ 54 ]. It is considered that biglycan expression is promoted by AKT activation even in diabetes showing hyperinsulinemia, which activates AKT [ 55 , 56 ]. On the other hand, biglycan expression is induced in tumor vascular endothelial cells by promoter demethylation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%